Climate Change Adaptation and Mitigation Strategies for Small Holder Farmers: A Case of Nyanga District in Zimbabwe - Mushore, Terence Darlington; Mhizha, Teddious; Manjowe, Moven; Mashawi, Linia; Matandirotya, Electdom; Mashonjowa, Emmanuel; Mutasa, Collen; Gwenzi, Juliet; Mushambi, George Tawanda (Frontiers in Climate, 2021)
Climate change encompassing mostly hydro-meteorological hazards is a reality affecting the world in diverse ways. It is manifesting in various ways such as increases in frequency and intensity of floods, droughts and extreme temperatures. In recent years, climate change has induced droughts, other extreme weather events and meteorological disasters in many countries including Zimbabwe.Effective management of climate change induced challenges require localized strategies which may vary from one part of the world to another and even within a country. In view of the need to understand localized impacts and responses to climate change, the main objectives of the study were to (i) assess the impact of climate change on livelihoods and food security, (ii) identify and evaluate adaptation and mitigation strategies that small holder farmers in Ward 17, Nyanga, Zimbabwe have developed. The research used both qualitative and quantitative approaches with data collection methods comprising of questionnaires (56), observations and interviews (8). The tools were used to gather information which included encounters with extreme weather events, climatic trends as well as adaptive responses. The findings showed that climate change had a significant negative impact on the livelihoods and food security status of small holder farmers in ward 17 of Nyanga district. The identified climate change adaptation strategies implemented in the study area included food aid, use of traditional grains and other drought resistant crops, early planting, multiple planting, barter trade and livelihood diversification. The mitigation strategies used included afforestation and reforestation programs, avoiding veld fires and preservation of wetlands. The research identified challenges to climate change adaptation which include lack of markets to sell farming produce, inefficient institutions, poverty and high climate variability and increased uncertainty in the behavior of seasons. The findings of this study indicated the need for similar assessment in other parts of the country as impacts of climate change and responses thereof should vary from place to place.